Reliability Design of Grid-connected Wind Turbine - 王立鹏; 刘红文 (Kongzhi Yu Xinxi Jishu)
Reliability index and evaluation of grid-connected wind turbine is introduced, and the operation situation is also described. Reliability design of grid-connected wind turbine is made based on its reliability series model, which can find out the weak link and enhance the reliability to realize increasing the availability and annual power output of wind turbine.